Bone marrow mesenchymal stem cells-derived exosomal microRNA-124-3p attenuates hypoxic-ischemic brain damage through depressing tumor necrosis factor receptor associated factor 6 in newborn rats - Min, Weijie; Wu, Yina; Fang, Yibin; Hong, Bo; Dai, Dongwei; Zhou, Yu; Liu, Jianmin; Li, Qiang (Bioengineered, 2022)
Mesenchymal stem cells (MSCs)-derived exosomes (Exo) are beneficial in the use of brain damages. Restrictively, the mechanism of Exo expressing miR-124-3p in hypoxic-ischemic brain damage (HIBD) is not completely comprehended. Thereupon, this work was put forward to reveal the action of bone marrow MSCs-derived Exo (BMSCs-Exo) expressing miR-124-3p in the illness. BMSCs were isolated and transfected with miR-124-3p agomir. Then, BMSCs-Exo were extracted and identified. The newborn HIBD rats were injected with miR-124-3p-modified BMSCs-Exo or tumor necrosis factor receptor associated factor 6 (TRAF6)-related vectors. Next, neurological functions, neuron pathological and structural damages, oxidative stress and neuronal apoptosis were observed. miR-124-3p and TRAF6 expression was tested, along with their targeting relationship. miR-124-3p was down-regulated, and TRAF6 was up-regulated in newborn HIBD rats. miR-124-3p targeted TRAF6. BMSCs-Exo improved neurological functions, alleviated neuron pathological and structural damages, suppressed oxidative stress and reduced neuronal apoptosis in newborn HIBD rats, whereas BMSCs-Exo-mediated effects were enhanced by restoring miR-124-3p. Silencing TRAF6 attenuated HIBD in newborn rats, but overexpression of TRAF6 reversed the protective role of miR-124-3p-overexpressing BMSCs-Exo. This work makes it comprehensive that up-regulated exosomal miR-124-3p ameliorates HIBD in newborn rats by targeting TRAF6, which replenishes the potential agents for curing HIBD.